Hypoglycemic effect of flavonoid glabridin prevents homeostatic disruption of native achilles tendon in streptozotocin-induced type 1 diabetic rats - Jongdee Nopparat; Wipapan Khimmaktong; Chumpol Pholpramool; Chittipong Tipbunjong (Penerbit Universiti Kebangsaan Malaysia, 2023)
Diabetic mellitus is a complex and serious disorder characterized by poor glycemic control leading to tendon architectural alterations and inflammation. This study aimed to investigate the protective effects of glabridin, a polyphenolic flavonoid, on architecture and inflammation of the Achilles tendon in streptozotocin-induced type 1 diabetic rats. Type 1 diabetes was induced by a single intraperitoneal injection of streptozotocin (60 mg/kg b.wt.). After confirmation of the diabetic state, the rats were divided into four groups; normal control, diabetic control, diabetic + glabridin (40 mg/kg b.wt.), and diabetic + glyburide (5 mg/kg b.wt.) as a positive control group. After 8 weeks of treatment, the Achilles tendons were collected and subjected to histopathological examinations with hematoxylin and eosin, Masson’s trichrome, periodic acid Schiff, and toluidine blue staining. Immunohistochemical staining (IHC) was also performed to study the inflammation of the tendon tissues. Histopathological examinations showed the protective effects of glabridin against hyperglycemia-induced collagen disorganization and deposition of glycoproteins in the extracellular matrix of the tendon. Treatment with glabridin significantly decreased the interfibrillar length, interfibrillar space, and number of infiltrated mast cells in the tendon tissue of diabetic rats. In addition, IHC staining showed that administration of glabridin drastically attenuated advance glycation end products (AGEs) formation and accumulation, and decreased the IL-1β and TNF-α positive stains compared to the non-treated diabetic control group. Taken together, this study showed glabridin prevents architectural alterations and suppresses inflammation in the Achilles tendon of diabetic rats.